The Effect of Inflation and Unemployment on Poverty in Medan City 2001 - 2022 - Siburian, Rowinna (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
This research aims to explore the influence of inflation and unemployment on poverty levels in Medan City. The results of the analysis show that although inflation and unemployment have a positive impact, their impact is not significant on poverty in Medan City. This research adopts a quantitative approach, focusing on analyzing statistical data including inflation, unemployment and poverty rates in Medan City during the period 2001 - 2022. These data are processed using relevant statistical techniques and econometric models to identify and test the correlation between inflation and unemployment. and poverty by using the Eviws application. In the capital of North Sumatra Province, Medan City, macroeconomic problems that are still emerging are high rates of poverty and unemployment. These two problems have a direct impact on social welfare and economic growth in the city. Therefore, it is important to pay attention to and respond to these issues seriously, as they have significant implications for society and economic development in the region. Efforts to overcome poverty and unemployment in Medan City must be a priority in the regional economic development agenda.